Exploring invasiveness and versatility of used microhabitats of the globally invasive Gambusia holbrooki - Kurtul, Irmak; Tarkan, Ali Serhan; Sarı, Hasan Musa; Haubrock, Phillip J; Soto, Ismael; Aksu, Sadi; Britton, J Robert (The Science of the total environment, 2024)
Non-native species can lead to severe impacts on invaded ecosystems, including the decline of ecosystem function through deleterious impacts on species diversity. The successful establishment of non-native species in new environments is the first barrier a species must overcome, ultimately depending on its ability to either cope with or adapt to local site-specific conditions. Despite the widespread distribution and ecological consequences of many freshwater invaders, site-specific and climatic preferences are often unknown. This is also the case of the Eastern mosquitofish Gambusia holbrooki, a global invader considered as a pervasive threat to endemic species. Here, we determined the ecological features and preferred site-specific conditions of G. holbrooki in Türkiye, which spans a wide range of diverse biogeographically distinct ecosystems by surveying populations from 130 localities in 2016 and 2017. Gambusia holbrooki were detected by hand-net in 48 of these sites (19 lotic, 29 lentic). It showed a preference for shallow waters with medium sized rocks, and abundances differed spatially across a latitudinal gradient and was influenced predominantly by variations in pH. The only other factors predicting its presence were low current velocities and gravel substrate, highlighting its ecological versatility in utilising a wide range of microhabitats. Bioclimatic models suggest that G. holbrooki is found in areas with a wide average annual temperature ranging from 10 to 20 °C, but with temperature not being a limiting factor to its invasion. Gambusia holbrooki shows a preference for xeric freshwater ecosystems and endorheic basins, as well as temperate coastal rivers, temperate upland rivers, temperate floodplain rivers and wetlands, and tropical and subtropical coastal rivers. These results, particularly the wide occurrence with only few limiting factors, emphasise the invasion potential of mosquitofish and should substantiate the need for localised invasive species management and conservation efforts, particularly in smaller or insular areas where mosquitofish and endemic fish species co-exist.
Keywords: Habitat management; Animals; ekosystém; Fresh Water; Ecosystem; zvířata; Rivers; Poeciliidae; Introduced Species; Ecological valence; sladká voda; zavlečené druhy; Microhabitat preference; řeky; Cyprinodontiformes